Performance Management : A business process benchmarking approach - Rolstadås, Asbjørn (Springer Netherlands, 1995)
The modern way to improve productivity is by a process- oriented approach. This involves focusing on performance in a company rather than on efficiency. This new way of thinking, commonly referred to as business process re-engineering, is clearly discussed in this book. The book aims to provide readers with a detailed overview of performance measurement and productivity improvement techniques and practice.